An effective system for recovering recyclable waste from households in China: Ant Recovery's bottom-up scheme in Changchun city. (15th February 2022) - Steuer, Benjamin; Li, Huijie
Graphical abstract: Highlights: An effective waste recovery scheme of bottom-up 'formalised' informal collectors. Findings are based on 21 single-day field observations and over 470 interviews. Recovery capacity: 438.4 kg/hour per station, 2, 325.3 metric tons/day overall. Actual household waste generation is calculated for comparative analysis. Waste recovery is less dependant on financial incentives, rather on daily routines. Abstract: In light of China's rising environmental governance focus on household waste recycling, this article analyses a novel recyclable waste recovery scheme, Ant Recovery, in Changchun, Jilin Province. In contrast to other recyclable waste collection systems, Ant Recovery emerged as a bottom-up venture established by members of the informal recycling sector in cooperation with the local recycling association. To assess the scheme's performance, the analysis uses field research data obtained over 21 days of observatory and questionnaire surveys at one of Ant Recovery's mobile collection points. Based on data from 1, 501 documented recyclable waste transactions, the analysis indicates a median recovery rate of 438.4 kg/hour at the surveyed recovery station. Extended to the entire scheme's network in Changchun, the figure extrapolates to 2, 034.6 metric tons/day, which approximates to roughly 94% of waste recyclables generated by the city's households. These achievements essentially result from two factors: (1) A beneficial policy environment established by central and local regulations and (2) AR's operational compatibility with daily routines and profit orientation of waste recyclable delivering stakeholders. In comparison to many other recycling systems in China, the alternative model in Changchun appears to be indigenous with little requirement for novel organisational structures or high capital/ overhead costs.